Perbedaan Pengaruh Intervensi Ultrasound Menggunakan Aquasono Gel dibandingkan dengan Diclofenac Terhadap Penurunan Nyeri pada Kondisi â€œGolferâ€™s Elbow Syndromeâ€ (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2008)
This watchfulness aims to detect intervention influence difference ultrasound therapy by using aquasono gel and declofenac towards pain depreciation in golfers elbow. Watchfulness with quasi eksperimental, with design pre test post test control group design. Sample at make to be two groups that is group with intervention ulrasound use aquasono gel and group with intervention group ulrasound use menclofenac. Found pain reduction that have a meaning in part elbow in place tendon muscle flexor carpi radialis and pronator main, after done intervention ultrasound by using aquasono gel, with result t-test related, where demo that value p (=0,00) < Î± (=0,05) and value t count (= 28,2) > t table (=1,83). found pain reduction that have a meaning in part elbow in place ten-don muscle flexor carpi radialis and pronator main, after done intervention ultrasound by using menclofenac in voltaren emulgel with result t-test related, where demo that value p (=0,00) < Î± (=0,05) and t count (=1,83) < t table (=15,17), there influence difference that have a meaning between intervention ultrasound by using aquasono gel, with intervention ultrasound by using menclofenac in voltaren emulgel based on t-test independent demo that value p (= 0,01) < Î± (= 0,05) and t-hitung (= -3,19) > t-tabel (=2,10).Â Keywords: Golfers Elbow, Aquasono Gel, DeclofenacÂ